2005
DOI: 10.1007/s11064-005-2616-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Strychnine-sensitive Glycine Receptor in the Intact Frog Retina: Modulation by Protein Kinases

Abstract: We studied 3H-glycine and 3H-strychnine specific binding to glycine receptor (GlyR) in intact isolated frog retinas. To avoid glycine binding to glycine uptake sites, experiments were performed at low ligand concentrations in a sodium-free medium. The binding of both radiolabeled ligands was saturated. Scatchard analysis of bound glycine and strychnine revealed a KD of 2.5 and 2.0 microM, respectively. Specific binding of glycine was displaced by beta-alanine, sarcosine, and strychnine. Strychnine binding was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…Recently, the effects of receptor phosphorylation on specific binding of 3 H-Gly and 3 H-Str were investigated. The binding of both radioligands was remarkably reduced after phorbol ester activation in isolated frog retinas (Salceda and Aguirre-Ramirez, 2005 ), in agreement with our findings. In a similar study, specific radioligand binding after PKA or PKC activation was decreased by 60%–85%, an effect that could be blocked by specific kinase inhibitors (Velázquez-Flores and Salceda, 2011 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recently, the effects of receptor phosphorylation on specific binding of 3 H-Gly and 3 H-Str were investigated. The binding of both radioligands was remarkably reduced after phorbol ester activation in isolated frog retinas (Salceda and Aguirre-Ramirez, 2005 ), in agreement with our findings. In a similar study, specific radioligand binding after PKA or PKC activation was decreased by 60%–85%, an effect that could be blocked by specific kinase inhibitors (Velázquez-Flores and Salceda, 2011 ).…”
Section: Discussionsupporting
confidence: 92%
“…They observed that phosphorylation accelerated desensitization of glycine induced currents, in agreement with our data. A further phosphorylation study on 3 H-glycine and 3 H-strychnine specific binding to GlyRs in intact isolated frog retinas showed that specific binding of both radioligands was reduced 30%–90% after activation of PKA with 10 μM Forskolin (Salceda and Aguirre-Ramirez, 2005 ), in good agreement with reduced receptor activity after PKA treatment observed in this study. In case of α2 and α3 receptors, Ser-346, located within the PKA consensus sequence (R-E-S-R, not present in α1) of the GlyR α3 intracellular loop has proven to be an essential target for prostaglandin-E(2)-mediated phosphorylation.…”
Section: Discussionsupporting
confidence: 89%
“…Downstream events of such factor(s) could at least imply protein kinase activity. In that respect, it has been shown that, in the retina and in auditory nuclei, protein kinases modulate strychnine binding and, hence, GlyR expression (Salceda and Aguirre-Ramirez, 2005; Yan et al, 2007). Figure 1 summarizes the current findings on glycine and GlyR signalling in macroglial cells.…”
Section: Neuroglial Cellsmentioning
confidence: 99%
“…Sarcosine (aka N-methylglycine), is a glycine transporter 1 (GlyT1) inhibitor that can increase extracellular glycine (Lopez-Corcuera et al, 1998;Herdon et al, 2001) via blockade of GlyT1-mediated glycine uptake or through a hetero-exchange of sarcosine for glycine (Herdon et al, 2001). Sarcosine agonizes the glycine receptor (GlyR) via binding to its strychnine-sensitive site (Salceda and Aguirre-Ramirez, 2005;Zhang et al, 2009). In addition, sarcosine acts as a co-agonist of N-methyl-D-aspartate receptor (NMDAR) (Ryley Parrish et al, 2013).…”
Section: Introductionmentioning
confidence: 99%